Pembentukan Peraturan Presiden Sebagai Aturan Pelaksana Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 Untuk Perlindungan Anak Luar Kawin - Naini, Romlatust; Usanti, Trisadini Prasastinah; Sukardi, Sukardi (Notaire, 2023)
AbstractThe provisions of Article 43 paragraph (1) of the Marriage Law regarding the position of children out of wedlock have undergone changes, following the Constitutional Court Decision Number 46/PUU-VIII/2010. Due to the lack of certainty in addressing the criteria and rights of children out of wedlock in the provisions of Article 43 paragraph (1) of the Marriage Law. Meanwhile, there are no government regulations mandated in Article 43 paragraph (2) of the Marriage Law, which has an impact on the position of children out of wedlock. The aim of this research is to analyze the criteria, position and rights of children out of wedlock and the urgency of forming legislative regulations after the Constitutional Court Decision Number 46/PUU-VIII/2010. The methodology used in this research is normative legal research with a statutory approach, a conceptual approach and a legal reform approach. The results of this research indicate that there is a need for criteria related to the phrase "children born out of wedlock”, in this case the child in question can be interpreted as a child born from a marriage that is not registered, or can even be interpreted as child born without a legal marriage, it can also be interpreted otherwise as children born outside a marriage. This aims to avoid multiple interpretations and ensure the fulfillment of the rights of children out of wedlock. The urgency of forming Legislative Regulations after the Constitutional Court Decision Number 46/PUU-VIII/2010, has juridical implications, including firstly adjustments to laws relating to children, namely the Marriage Law, the Citizenship Law and the Child Protection Law. Secondly, implementation of the provisions of Article 43 paragraph (2) of the Marriage Law with the existence of government regulations to regulate and ensure the rights of children out of wedlock. Thirdly, the establishment of a Presidential Regulation as an implementing regulation for Constitutional Court Decision Number 46/PUU-VIII/2010 which provides protection for the position and rights of children out of wedlock.Keywords: Constitutional Court Decision Number 46/PUU-VIII/2010; Children Out of Wedlock; Formation of Legislation. AbstrakKetentuan Pasal 43 ayat (1) UU Perkawinan mengenai kedudukan anak luar kawin mengalami perubahan, pasca Putusan Mahkaman Konstitusi Nomor 46/PUU-VIII/2010. Hal ini dikarenakan belum adanya kepastian tentang kriteria, kedudukan dan hak anak luar kawin dalam ketentuan Pasal 43 ayat (1) UU Perkawinan. Disamping itu, belum adanya peraturan pemerintah yang diamanatkan pada Pasal 43 ayat (2) UU perkawinan sehingga berdampak pada kedudukan anak luar kawin. Tujuan dari penelitian ini adalah menganalisis kriteria, kedudukan dan hak Anak Luar Kawin dan Urgensi Pembentukan Peraturan Perundang-undangan Pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010. Metode penelitian ini adalah penelitian hukum normatif dengan pendekatan Perundang-Undangan (Statute Approach), pendekatan konseptual (Conceptual Approach) dan Pendekatan Pembaharuan Hukum (Legal Reform). Hasil penelitian ini menunjukkan bahwa perlu adanya kriteria terkait dengan frasa "anak yang dilahirkan di luar perkawinan”, dalam hal ini anak dimaksud dapat diartikan sebagai anak yang lahir dari perkawinan yang tidak dicatatkan, atau dapat pula diartikan sebaliknya sebagai anak-anak yang dilahirkan dari perkawinan orang tuanya yang tidak sah atau anak lahir tanpa perkawinan orang tuanya. Hal ini bertujuan agar tidak menimbulkan multitafsir dan menjamin terpenuhinya hak anak luar kawin. "Urgensi pembentukan Peraturan Perundang-undangan Pasca Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010”, membawa implikasi yuridis diantaranya Pertama penyesuaian terhadap undang-undang yang berkaitan dengan anak yakni UU Pekawinan, UU Kewarganegaraan, dan UU Perlindungan Anak. Kedua, Pelaksanaan ketentuan "Pasal 43 ayat (2) UU Perkawinan” dengan adanya peraturan pemerintah untuk mengatur dan menjamin secara pasti hak-hak anak luar kawin. Ketiga Pembentukan Peraturan Presiden sebagai aturan pelaksana terhadap "Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 yang memberikan perlindungan kepada kedudukan dan hak-hak anak luar kawin. Kata Kunci: Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010; Anak Luar Kawin; Pembentukan Peraturan Perundang-undangan.